2018
DOI: 10.17016/2380-7172.2199
|View full text |Cite
|
Sign up to set email alerts
|

High-frequency Spending Responses to the Earned Income Tax Credit

Abstract: This survey and report were prepared by the Consumer and Community Development Research Section of the Federal Reserve Board's Division of Consumer and Community Affairs (DCCA). DCCA directs consumer-and community-related functions performed by the Board, including conducting research on financial services policies and practices and their implications for consumer financial stability, community development, and neighborhood stabilization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 13 publications
0
20
0
Order By: Relevance
“…The longer window did not materially change the results, and estimated coefficients for 7 to 21 days after the storm were not statistically different from zero. 22 See Aladangady et al (2016) and Aladangady et al (2018).…”
Section: Resultsmentioning
confidence: 99%
“…The longer window did not materially change the results, and estimated coefficients for 7 to 21 days after the storm were not statistically different from zero. 22 See Aladangady et al (2016) and Aladangady et al (2018).…”
Section: Resultsmentioning
confidence: 99%
“…Maag et al (2016) This study contributes to the literature in several ways. First, to our knowledge, only a single study has investigated the impact of the PATH Act for low-income households, finding that refund delays affect spending on essential purchases, such as groceries and non-durable goods (Aladangady et al, 2018). Besides the unique contribution to the scarce literature on the recent PATH Act reform and on the timing of refund payments in general, an additional advantage of our study is that we use administrative individual-level tax data to precisely estimate which households receive the EITC, the amount of federal tax refund they receive, and the exact date of tax filing.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…EITC and ACTC filers tend to file their taxes much earlier in the tax season than filers not claiming these credits; 56 percent of LMI online tax filers using free, online tax filing software and claiming the EITC or ACTC filed their taxes before February 15 in 2016 (Maag, Roll, and Oliphant 2016), suggesting that roughly half of this population could be potentially affected by a multiple-week delay. An analysis of IRS data also indicates that the issuance of EITC and ACTC refunds was delayed by an average of two weeks in 2017, relative to prior tax seasons (Aladangady et al 2018). Additionally, the number of RALs-which allow tax filers to borrow against their anticipated refund amount in order to get immediate access to the funds promised by the refund-almost quadrupled between 2016 and 2017 (Aladangady et al 2018; see footnote 7).…”
Section: The Path Act and Tax Refund Delaysmentioning
confidence: 99%
See 1 more Smart Citation
“…The early empirical literature suggested that MPCs were small for large shocks (Hsieh, 2003). However, new empirical evidence has overturned this finding (Kueng, 2018), and shown that MPCs remain sizeable even in response to large income shocks (Kueng, 2018;Fuster, Kaplan, and Zafar, 2018;Aladangady et al, 2018;Bunn et al, 2018;Fagereng, Holm, and Natvik, 2019). This new empirical evidence is difficult to rationalize in traditional two-asset models, where the consumption response to large income shocks is negligible.…”
Section: Introductionmentioning
confidence: 99%